ANALISIS KEMAMPUAN CURRENT RATIO, RETURN ON TOTAL ASSETS, DEBT TO TOTAL ASSETS, TOTAL ASSETS TURNOVER, DAN PRICE EARNING RATIO DALAM MEMPREDIKSI PERTUMBUHAN LABA PADA PERUSAHAAN MANUFAKTUR DI BEI TAHUN 2013-2017 - Frenita Damayanti Damayanti; Lardin Korawijayanti Korawijayanti; Tutik Dwi Karyanti (Politeknik Negeri Semarang, 2020)
This study aims to examine the effect of current ratio, return on total assets, debt to total assets, total asset turnover, and price earning ratio in predicting profit growth both simultaneously and partially. The sample in this study were 55 manufacturing companies listed on the Indonesia Stock Exchange during 2013-2017.The collected data will be processed and then analyzed using multiple linear regression. The test is carried out using the help of the SPSS for Windows program.The results of the analysis show that the current ratio, return on total assets, debt to total assets, total asset turnover, and price earning ratio simultaneously influence in predicting earnings growth. Partially, only return on total assets and total assets turnover has a significant effect on predicting earnings growth. The value of adjusted R square is 7,7%. This means that 7,7% of profit growth can be explained by independent variable (current ratio, return on total assets, debt to total assets, total asset turnover, and price earning ratio). While the remaining (92,3%) is explained by other variables or other causes.